Construction of a Science Teacher's Topic-Specific Pedagogical Content Knowledge in the Gifted Class - Burak Çaylak; Jale Çakıroğlu (e-Kafkas Eğitim Araştırmaları Dergisi)
This study examines a science teacher's pedagogical content knowledge during instruction on the topics work and energy, simple machines, and friction force in a gifted class. The research adopts a single case study approach, employing qualitative methods. The participant is a middle school science teacher, and data collection tools include interviews, observations, card-sorting activities, and lesson plans. The study’s data were analyzed in an in-depth analysis of explicit PCK. The main findings of the study are: (1) gifted students required additional science practice beyond the scope of the traditional curriculum, (2) the participating teacher encountered challenges when designing and implementing enrichment activities, (3) the characteristics of gifted students positively influenced the development of the teacher's pedagogical content knowledge, and (4) the presence of gifted students prompted a shift in the teacher's science teaching orientation from traditional methods to reform-based practices. Teachers need to have additional knowledge bases or pedagogical content knowledge components. Notably, the research underscores the relevance of the knowledge of enrichment curriculum and knowledge of characteristics of gifted students in the training of science teachers, along with the crucial role of STO in the education of gifted students, especially in the context of teaching physics. These findings offer significant implications for the curriculum designed for gifted students, particularly concerning the teaching and learning of physics topics.